Rock Physical Model and AVO Patterns for the Mud-Rich Source Rock - Yu, Songhe; Zong, Zhaoyun; Yin, Xingyao (Frontiers in Earth Science, 2021)
Rock physical model and AVO patterns considering organic matter content and minerals composition are of significance to guide the identification and prediction of the mud-rich source rock. A rock physical model describing the elastic properties of kerogen at different maturity stages is proposed. The proposed rock physical model builds intrinsically connection between elastic properties and physical parameters of the mud-rich source rock, thereby provides the theoretical basis for seismic inversion and seismic forward modeling. To overcome the limitation of laboratory measurement, a combination-four-parameter regression method is further proposed to estimate the continuous TOC (total organic carbon) values for the verification and analysis of the rock physical model. Modeling results reveal that the P-wave velocity and P-wave impedance will decrease with the increase of TOC, and the Poisson ratio and Poisson impedance will increase as the mud content increasing, which are consistent with the conclusions of the crossplot using actual well data. Based on the proposed rock physical model, the seismic responses of the mud-rich source rock are further modeled. The synthetic seismic records are consistent with the well-side seismic records and the top reflection of the mud-rich source rock behaves a stronger negative event diming with the incident angle and corresponds to class IV AVO pattern, and the bottom reflection exhibits class I AVO anomaly. In addition, a two-layer model is constructed to analyze the effect of TOC content and mud content on the AVO characteristics. The results indicate that increasing TOC content and mud content will significantly increase the intercepts and slightly change the gradients of the PP reflection coefficients. These results help to guide the identification and evaluation of the mud-rich source rock.